MENINGKATKAN HASIL BELAJAR MATERI MASYARAKAT DI DAERAHKU DENGAN MEDIA DIORAMA PADA PESERTA DIDIK KELAS IV SDN KEBONSARI 1/414 SURABAYA - Wulan Anggraini; Delia Indrawati; Ganda Riswanto; Sri Yuniati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The focus of this research is the learning material of the community in my area in class IV of SDN Kebonsari 1/414 Surabaya, where students experience difficulties in understanding concepts. The main factors causing this are insufficient use of learning media and ineffective conventional teaching methods. Diorama media was used in this research to improve student learning outcomes. Planning, implementation, observation, and reflection are components of these two cycles of classroom action research. The research results show that the use of diorama media significantly improves student learning outcomes. The average score increased from 19% in cycle I to 88% in cycle II, and the percentage of completeness increased from 45.38% to 85.77%.